Skyline tensile forces in cable logging : field observations vs. software calculations - Mologni, Omar (Array, 2021)
Skyline tensile forces have been shown to frequently exceed the recommended safety limits during ordinary cable logging operations. Several models for skyline engineering analyses have been proposed. Although skyline tensile forces assume a dynamic behaviour, practical solutions are based on a static approach without consideration of the dynamic nature of the cable systems.The aim of this study was to compare field data of skyline tensile forces with the static calculations derived by dedicated available software such as SkylineXL. To overcome the limitation of static calculation, this work also aimed to simulate the actual response of the tensile fluctuations measured in the real environment by mean of a finite element model (FEM).Field observations of skyline tensile forces included 103 work cycles, recorded over four different cable lines in standing skyline configuration. Payload estimations, carriages positions, and time study of the logging operations were also collected in the field. The ground profiles and the cable line geometries were analysed using digital elevation models. The field data were then used to simulate the work cycles in SkylineXL. The dynamic response of six fully-suspended loads in a single-span cable line was also simulated by a dedicated FEM built through ANSYS®. The observed data and the software calculations were then compared.SkylineXL resulted particularly reliable in the prediction of the actual tensile forces, with RMSE ranging between 7.5 and 13.5 KN, linked to an average CV(RMSE) of 7.24%. The reliability in predicting the peak tensile forces was lower, reporting CV(RMSE) of 10.12%, but still not likely resulting in a safety or performance problem. If properly set-up and used, thus, SkylineXL could be considered appropriate for operational and practical purposes.